Peran Komunitas Harapan dalam Pendampingan Anak Rentan di Kampung Sumeneban, Kota Semarang - Muti'ah, Lafiya Nailal; Rini, Hartati Sulistyo (Universitas Lambung Mangkurat, 2026)
Children are a vulnerable group at risk of experiencing rights violations, especially in urban areas with densely populated settlements and limited social support. This study aims to analyze the role of Komunitas Harapan in assisting vulnerable children in Kampung Sumeneban, Semarang City, as well as to examine the challenges and vulnerabilities of community-based assistance sustainability through the perspective of Robert D. Putnam's social capital. This study uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, with validity tested through triangulation of sources, techniques, and time. Data analysis used an interactive analysis model carried out continuously until saturation was reached. The results of the study show that Komunitas Harapan plays a role in providing educational assistance, character building, and social support. These mentoring practices build social capital in the form of social networks, social norms, and trust among volunteers, children, parents, and external partners. The study also identified challenges such as a limited number of volunteers and funding, the absence of standardized learning modules, and limited facilities. Moreover, social capital vulnerability is marked by disruptions in networks due to volunteer turnover and organizational structure uncertainty, decreased trust due to limited resources, and weakened institutional norms due to the dominance of volunteerism values. The novelty of this study lies in employing a sociological approach based on social capital analysis, highlighting the elements of social networks, social norms, and trust in the context of mentoring vulnerable children in urban areas.